AKUNTANSI PENGELUARAN KAS - Benaya S Hutagalung; Kenny Brighi Milala; Muhammad Rafly Fachrezy (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2024)
The cash disbursement accounting system is an essential component of the Accounting Information System (AIS), designed to ensure that every company expenditure is executed accurately, authorized properly, efficient, and fully accountable. Cash disbursements are carried out through two primary mechanisms: the use of checks for high-value transactions and petty cash funds for smaller or urgent payments. Through the utilization of documents such as cash disbursement vouchers, checks, petty cash vouchers, and accounting records including the cash disbursement journal and check register, the system supports a structured recording and monitoring process. The application of the imprest system and the fluctuating fund balance system in managing petty cash enables companies to maintain effective internal control while ensuring smooth operational activities. Additionally, segregation of duties, authorization procedures, and systematic documentation play an important role in minimizing the risk of fund misuse. Overall, the cash disbursement accounting system significantly contributes to enhancing transparency, payment efficiency, the utilization of purchase discounts, as well as maintaining the company’s financial health and reputation. Keywords: Accounting Information System, Cash Disbursement, Checks, Petty Cash, Imprest System, Fluctuating System, Internal Control, Cash Disbursement Voucher.